Nonperturbative free energy and phase transition for a complex scalar field theory - Ferreira, Matheus Curado (2022)
In this work we study thermal and chemical potential contributions to the mass at two loops and to the free energy at three loops for a charged scalar field. We also make use of the optimized perturbation theory to obtain nonperturbative results and for the phase transition analysis of the model at finite temperature and chemical potential, in the high temperature approximation.